The Strategy Of Islamic Religious Education Teacher In Forming Students' Akhlakul Karimah At MTs Nahdhatul Islam Mangang - Nadila Ananda Hidayat (Al-Ulum: Jurnal Pendidikan Islam, 2023)
This study aims to determine the strategies used by PAI teachers to shape the morals of students. Collecting this data the author uses a case study approach with qualitative research methods. The results of this discussion show that the moral formation carried out by PAI teachers is by maintaining cleanliness, caring for people and being able to be responsible for what has been implemented. While the strategy used by PAI teachers to shape the morals of students is by giving examples to students, getting used to praying Dhuha and midday prayers in congregation, and reading the Al-Qur'an together so that students have noble morals.